Hermeneutic Study: The Meaning of Lyric From Kebalai Singing In Rote Ndao Society (Universitas Negeri Semarang, 2022)
Traditional art through music, dance and even traditional rituals becomes a symbol and identity of the community because it is a reflection of collective thoughts and also regional solidarity. Kebalai is a dance danced by the people of Rote and is very famous. The kebalai does not only contain dances but also songs in the form of rhymes which are performed together in every event, from big events such as when. The poetry uses the Rote regional language and the meaning of each song is different. This makes researchers interested in looking at oral literature through the songs from the balai and efforts to document the meaning of the poem from the kebalai entitled